Indentifying published studies of care home research: an international survey of researchers - Burton, Jennifer K.; Quinn, Terence J.; Gordon, Adam L.; MacLullich, Alasdair M.J.; Reynish, Emma L.; Shenkin, Susan D. (Serdi, 2017)
Collating the published research around institutional, long term care is confounded by the differing terminologies used to describe this health-care setting. We aimed to collate the descriptors used by researchers to inform the future development of a ‘search filter’ (a collection of search terms to help identify relevant records from electronic literature databases). We surveyed international researchers via the Nursing Home Research International Working Group, European Geriatric Medicine Society and published reviewers, achieving at 38% response rate across 21 countries. Our findings identified variation in terminology used by researchers to describe long-term care settings in their country of practice. Nursing home was the most accepted term (96%). ‘Homes for the Aged’ was selected by 48% of respondents. A range of terms are likely to be necessary to identify all relevant research and these may not be intuitive. We will use these data to help inform development of a search filter.